Concurrent Refractory Atopic Dermatitis and Generalized Vitiligo Successfully Treated with Abrocitinib: A Case Report - Shao X; Pan X; Chen Y; Zhu Y; Chen S; Chen J (Journal of Asthma and Allergy)
Xinyi Shao,* Xingyu Pan,* Yangmei Chen, Yan Zhu, Shuang Chen, Jin Chen Department of Dermatology, The First Affiliated Hospital of Chongqing Medical University, Chongqing, 400010, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shuang Chen; Jin Chen, Department of Dermatology, The First Affiliated Hospital of Chongqing Medical University, No. 1 Youyi Road, Yuzhong District, Chongqing, 400016, People’s Republic of China, Tel +8617726638759 ; +8615023188592, Email 179409599@qq.com; chenjin7791@163.comAbstract: Atopic dermatitis (AD) may sometimes be comorbid with vitiligo. However, these therapeutic agents are often slow acting and lead to various adverse effects, resulting in poor patient compliance. This report describes a 65-year-old male patient with refractory moderate-to-severe atopic dermatitis (AD) and generalized vitiligo. The patient was treated with repeated antihistamine and dupilumab injections; however, erythema and pruritus did not improve. Consequently, oral abrocitinib was administered to treat AD and vitiligo, and the patient’s generalized erythema, papules, and pruritus ameliorated with the repigmentation of vitiligo lesions. This case provided evidence of the efficacy and safety of oral abrocitinib for patients with concurrent refractory AD and vitiligo.Keywords: atopic dermatitis, vitiligo, abrocitinib, JAK inhibitors